1991
DOI: 10.3168/jds.s0022-0302(91)78575-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Scrotal Insulation on Viability Characteristics of Cryopreserved Bovine Semen

Abstract: The effect of a 48-h scrotal insulation on spermatozoal viability (motility and acrosomal integrity), before and after semen cryopreservation, was studied in six young Holstein bulls whose semen was collected twice in succession at 3-d intervals. Motility and acrosomal integrity were measured before and after incubation of semen at 37 degrees C for 3 h. For assessment of results, collection days were grouped: period 1 (control) = d -6, -3, and 0, where d 0 = initiation of scrotal insulation after semen collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
33
1
4

Year Published

1997
1997
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(49 citation statements)
references
References 9 publications
5
33
1
4
Order By: Relevance
“…Although the epididymis has previously been reported to be resistant to heat [43], heat stress could disturb epididymal maturation of the spermatozoa because heat stress has been shown to damage the chromatin structure of sperm in the epididymis of the mouse [44] and the bull [45]. The results of this study have shown that heat stress significantly reduced sperm concentration, motility, viability, but increased the number of abnormal spermatozoa.…”
Section: Discussionmentioning
confidence: 71%
“…Although the epididymis has previously been reported to be resistant to heat [43], heat stress could disturb epididymal maturation of the spermatozoa because heat stress has been shown to damage the chromatin structure of sperm in the epididymis of the mouse [44] and the bull [45]. The results of this study have shown that heat stress significantly reduced sperm concentration, motility, viability, but increased the number of abnormal spermatozoa.…”
Section: Discussionmentioning
confidence: 71%
“…Although sperm at various stages of development or in the epididymis may be affected by increased testicular temperature (Lue et al 1999;Perez-Crespo et al 2008;Hamilton et al 2016), in our study, due to the delay from testicular heating to appearance of abnormalities, there was no apparent effect on sperm present in the epididymis. However, in a previous study in bulls with scrotal insulation (Vogler et al 1991), sperm present in the epididymis were apparently unaffected when fresh, unfrozen sperm were evaluated, although changes were evident after sperm cryopreservation, thawing, and incubation for 3 h at 37 °C.…”
Section: Discussionmentioning
confidence: 99%
“…O aumento da temperatura testicular propicia a degeneração seminal (MOORE, 1924;PHILIPS e McKENZIE, 1934;VOGLER et al, 1991), está correlacionada com a redução na fertilidade do macho (GUNN et al, 1942;HULET et al, 1956) e causa alterações na síntese de proteínas e expressão de gens nas células germinativas e células de Sertoli (IKEDA et al, 1999;GUO et al, 1999;KUMAGAI et al, 1999). Variações na temperatura ambiente e umidade relativa do ar também estão associadas a alterações na temperatura corporal de carneiros e, consequentemente, na temperatura testicular (FOOTE et al, 1957;WILDEUS e ENTWISTLE, 1983).…”
Section: Rev Bras Zootec 30(6):1704-1711 2001unclassified